A magnetoreception system constructed by a dysprosium metallofullerene and nitroxide radical. Issue 28 (29th June 2017) - Li, Yongjian; Wang, Taishan; Zhao, Chong; Qin, Yu; Meng, Haibing; Nie, Mingzhe; Jiang, Li; Wang, Chunru
Abstract : A site-specific magnetoreception system between Dy3 N@C80 and nitroxide radical through spin-paramagnet interaction. Abstract : Endohedral lanthanide metallofullerene molecules exhibit various paramagnetic properties. In this study, we present a magnetoreception probe that can detect the magnetic properties of an endohedral metallofullerene via spin-paramagnet interaction between a nitroxide radical and Dy3 N@C80 . A cycloaddition reaction on the outer cage of Dy3 N@C80 was employed to obtain two regioisomers linked with the nitroxide radical; the resultant adduct exhibits site-dependent signal intensity in the ESR spectra. This Dy3 N@C80 -nitroxide radical adduct has potential applications as a molecular compass with position-sensitive magnetoreception ability.